Protection of Other Religious Sanctities for Interfaith Harmony in The Light of Sirah of Holy Prophet Muhammad (PBUH) - Hafiz Fazale Haq Haqqani; Prof. Dr. Shah Moeen Ud Din Hashmi (Al Manhal Research Journal, 2024)
The protection of religious sanctities is a fundamental aspect of interfaith harmony and societal cohesion. This paper explores the principles and practices related to the protection of other religious sanctities as exemplified in the Sirah (biography) of the Holy Prophet Muhammad (PBUH). By analyzing the Prophet's interactions with non-Muslim communities and his approach to their places of worship and religious symbols, this study highlights how his actions and teachings underscore the importance of respecting and safeguarding the sanctities of all faiths. The research draws on primary sources such as Hadith and Sirah literature and contextualizes these within broader Islamic ethical frameworks. It argues that the Prophet Muhammad's (pbuh) model of respect and protection for other religious sanctities offers a timeless guide for fostering mutual respect and coexistence in a diverse world. This investigation not only contributes to a deeper understanding of Islamic teachings on interfaith relations but also offers valuable insights for contemporary dialogue and conflict resolution among different religious communities.